2021
DOI: 10.1111/1365-2435.13881
|View full text |Cite
|
Sign up to set email alerts
|

Mucilage binding to ground protects seeds of many plants from harvester ants: A functional investigation

Abstract: 1. The seeds of many plant species produce mucilage on their surfaces that when wetted and dried, firmly adheres seeds to surfaces and substrates. Previous studies have demonstrated that seed anchorage to the ground can reduce seed predation, although only a few species have thus far been tested.2. Here we investigated whether binding to the ground reduces seed removal by harvester ants Pogonomyrmex subdentatus, an important granivore, for 53 species with mucilaginous seeds. We also explored functional traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 86 publications
1
62
2
Order By: Relevance
“…Dislodgement force, especially that of dried mucilage was the most important predictor of dislodgement resistance (Dried mucilage dislodgement: partial R 2 = 0.26, CI 95 = [0.00012, 0.50], Wet mucilage dislodgement: partial R 2 = 0.076, CI 95 = [-0.094, 0.31]). It correlated strongly with mucilage mass, a result we also found with a different set of species and a slightly different dislodgement assay (Pan et al, 2021), suggesting that increased dislodgement force can be driven by simply increasing mucilage production. Mucilage mass may be quite variable among close relatives (Table S2).…”
Section: What Drives Dislodgement Force?supporting
confidence: 55%
See 4 more Smart Citations
“…Dislodgement force, especially that of dried mucilage was the most important predictor of dislodgement resistance (Dried mucilage dislodgement: partial R 2 = 0.26, CI 95 = [0.00012, 0.50], Wet mucilage dislodgement: partial R 2 = 0.076, CI 95 = [-0.094, 0.31]). It correlated strongly with mucilage mass, a result we also found with a different set of species and a slightly different dislodgement assay (Pan et al, 2021), suggesting that increased dislodgement force can be driven by simply increasing mucilage production. Mucilage mass may be quite variable among close relatives (Table S2).…”
Section: What Drives Dislodgement Force?supporting
confidence: 55%
“…Their mucilage composition and primary function of mucilage in nature is thus far unknown but deserves more investigation. We have found that it provides a defensive benefit against harvester ants to several Polemoniaceae species (LoPresti et al, 2019, Pan et al, 2021, though it was similarly not as protective compared to other families in those studies.…”
Section: What Drives Dislodgement Force?mentioning
confidence: 54%
See 3 more Smart Citations